William Crawford Gorgas papers - Gorgas, William Crawford, 1854-1920.; Gorgas, Josiah, 1818-1883.
Correspondence, addresses, reports, articles, medical papers, financial records, clippings, printed matter, charts, photographs, and other papers relating chiefly to Gorgas's work in combating yellow fever in Florida and Latin America, in particular Cuba and Panama. Includes materials used in preparation of a report on Latin America by the Rockefeller Foundation Yellow Fever Commission. Also includes extracts of a journal of Confederate officer Josiah Gorgas chronicling the Civil War and Reconstruction and Gorgas family correspondence. Correspondents include James L. Bevans; James Ten Broeck Bowles; Thomas Barbour; Henry Rose Carter; William M. Doughty; F.A. Ferris; Carlos Juan Finlay; John Guiteras; William W. Keen; C.C. McCulloch, Jr.; S. Weir Mitchell; G.R. Plummer; Claus Karl Schilling; George T. Stevens; and George Miller Sternberg.
Army medical officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bevans, James L. -- 1869-1944 -- Correspondence; Bowles, James Ten Broeck -- Correspondence; Barbour, Thomas, -- 1884-1946 -- Correspondence; Carter, Henry Rose, -- 1852-1925 -- Correspondence; Doughty, William M. -- 1881-1944 -- Correspondence; Ferris, F. A. -- -1918 -- Correspondence; Finlay, Carlos Juan, -- 1833-1915 -- Correspondence; Guiteras, John, -- 1852-1925 -- Correspondence; Keen, William W. -- 1837-1932 -- Correspondence; McCulloch, C. C. -- 1869-1928 -- Correspondence; Mitchell, S. Weir -- 1829-1914 -- Correspondence; Plummer, G. R. -- Correspondence; Schilling, Claus Karl, -- 1871-1946 -- Correspondence; Stevens, George T. -- 1832-1921 -- Correspondence; Sternberg, George Miller, -- 1838-1915 -- Correspondence; Gorgas family -- Correspondence; Confederate States of America. -- Army -- Officers; United States. -- Army -- Medical care; United States. -- Army -- Surgeons; Rockefeller Foundation. -- Yellow Fever Commission; Medicine -- Cuba; Medicine -- Florida; Medicine -- Latin America; Medicine -- Panama; Public health -- Cuba; Public health -- Florida; Public health -- Latin America; Public health -- Panama; Reconstruction (U.S. history, 1865-1877); Yellow fever -- Cuba; Yellow fever -- Florida; Yellow fever -- Latin America; Yellow fever -- Panama; Southern States -- History -- 1865-1877.; United States -- History -- Civil War, 1861-1865.; United States -- History -- 1865-1898.; Army officers; Physicians